THE HISTORY OF TRADE OF THE NUSANTARA IN THE 17th CENTURY - Budi Sulistiono (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2021)
The increasingly significant influence of Islam in the Archipelago was marked by the establishment of a number of sultanates. It is time for the existence of the sultanate to be interpreted as evidence of political power. The track of Islam in the Archipelago, political power was achieved after great successes in building ECONOMIC POWER, EDUCATION, CULTURAL-INTELLECTUAL NETWORKS. Therefore, the track of Islam in the Archipelago, is not an event that is considered strange. Until the 17th century AD, there were even a number of sultanates on the islands of Java, Kalimantan, Sulawesi, Maluku. The spread of the existence of a number of these sultanates in a relay as evidence of the results of the exemplary performances of a number of sultanates that had existed before. May we all never forget the existence of the Sultanate of Jeumpa (± 776 AD-880 AD), Peureulak (standing ± 840 AD), Samudera Pasai (± 1267 AD), Demak (1468 AD), Aceh Darussalam (1496 AD), Ternate (Maluku). ) rulers converted to Islam in 1460, Cirebon (founded 1479 AD), Banten (1526 AD), Banjar (founded 1520 AD). From the coast of Aceh-Malacca-Sumatra, Islam then spread in various directions east to areas on the north coast of Java such as Surabaya, Gresik, Tuban, then continued eastward to areas of Kalimantan, Sulawesi, Ternate and Tidore in the Maluku islands, Papua, Nusa Tenggara, Bali. The approach used in this paper is a historical approach by utilizing study materials from historical literature. In compiling historical facts, guided by logical arrangement of frameworks in chronological order. The conclusion is that, thanks to the wealth and social forces empowered by Muslim communities in various places in the Archipelago, they can play political roles in political entities as evidenced by the birth of a number of Sultanates. This historical fact, at least strengthens Anthony Reid's theory, that the maritime economy is an indicator of maritime trade that unites trade routes with the formation of port cities as international trade routes.